YIELD ACHIEVEMENT AND GAP COMPLIANCE AMONG THE PARTICIPANTS OF OIL PALM REPLANTING (TSSPK) & NEW PLANTING (TBSPK) SCHEME - Rahmahwati Rasuddin; Norkaspi Khasim; Mohd Noor Izuddin; Humaira M.T; Mohd Haidhar; Ainul Shazwin Sahidan; Mohd Ridzuan Sohimi, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The Malaysian government has set up various incentives to help farmers, including the Oil Palm Replanting (TSSPK) and New Planting Schemes (TBSPK) for oil palm independent smallholders (OPISH) which were implemented in 2011 under the 10th Malaysia Plan. It is an Entry Point Project 1 (EPP1) under the National Key Economic Area (NKEA) of oil palm commodities. The schemes provided farmers with high-quality seedlings, agricultural inputs such as fertilizers and chemicals, as well as a cash fund for the preparation of land and planting of the seedlings. The farmers who participated in the scheme were also given advisory services on various aspects of the management of oil palm by the extension officers of MPOB (TUNAS). A total of 400 participants were involved and responded to the survey, with the proportion of respondents from Peninsular, Sabah, and Sarawak. The study found that the average age of the participants is mostly above 59 years old (37.3%) and 44.3% of the participants were owners of oil palm farms. The main objectives of the study were to determine the current yields achieved by the participants in the scheme and their compliance with the GAP guidelines. This is a quantitative study, which applied the questionnaire approach in gathering data. It was found that 61.0% of farmers categorized as medium yield of FFB production who produced 21.5 - 28.9 ton/ha/year with average income received RM1500 - RM3000 per month, while 32.5% of farmers produced in a lower category (< 21 ton/ha/year), and there were 6.5% farmers produced more than 29 ton/ha/year that was considered as the higher yield of FFB production. This study also showed that most of the respondents complied with Good Agriculture Practice (GAP) after joining the scheme. Participants responded well to the services given by the TUNAS officers. Most of the participants were satisfied with the implementation of the schemes and services provided by TUNAS officers. As a recommendation, several improvements were suggested, such as agriculture input distribution, clustering of the farmers into cooperatives, and continuity of GAP implementation.